(untitled) (Journal of Engineering, 2024)
Residential complexes have witnessed a great demand in most countries worldwide, as they are one of the main infrastructure elements, in addition to achieving a developed urban landscape. However, complex residential projects in developing countries face various factors that could be improved in their implementation, especially in Iraq. Sixty-two experts in residential complex projects were interviewed and surveyed to verify these projects’ failure factors,. Fifty-one factors were the main failure factors, divided into four main components (leadership, management system, external forces, and project resources). The Relatively Important Index (RII) is used to determine the relative importance factors and obtain the top twelve factors that cause the optimal failure factors, correspondingly: political interference (87.7%), change in governments (86.5%), partisan politics available (85.6%), Unclear strategic planning (84.3%), inadequate planning (84.3%), lack of materials and equipment (83.3%), the poor obligation for project leaders (82.6%), work suspension due to demonstrations (82.3%), lack of human capacity (81.8%), bureaucracy (81.7%), corruption (81.4%), and misalignment in culture or ethics (81.3%). The achieved RII readings were high for leadership (73.1%), followed by project resources (71.3%), management systems (70.5%), and external forces (69.9%). The study recommended addressing the problems of implementing complex residential projects and solving the crisis to start the state’s economic growth phase according to new foundations and standards.